Nourishing Cultures: An Interview with Farangis Nurulla-Khoja - Hron, Terri; Nurulla-Khoja, Farangis (Circuit)

(untitled) (Circuit, musiques contemporaines, 2023)
In this interview with Terri Hron, Tajik-Québécoise composer Farangis Nurulla-Khoja describes moving from Tajikistan to study in Europe, and eventually, to live and work in Canada. She speaks of her experience composing a series of chamber ensemble works using poetry about the refugee experience. She shares her thoughts on being an immigrant composer in Quebec and Canada and the challenges and successes she has experienced. These include creating music in collaboration with oriental and occidental instrumentalists and finding inventive ways of working and notating.